The specifics of technical and tactical training of elite level wrestlers - Latyshev, S. V. (Theory and Practice of Physical Culture, 2025)
Objective of the study - is to identify the specific features of the technical and tactical readiness of elite-level wrestlers. For this purpose, an analysis of the universal principles that guide these athletes during competitive fights was carried out.